Analysis of Interjections in the Film 同桌的你 (My Old Classmate) and the Implications for Mandarin Language Learning - Rhesia, Naomi; Sitaresmi, Dhatu (Universitas Pendidikan Mandalika, 2024)
Interjections are a type of word that has the main function of emphasizing human emotions and intent or purpose. This research aims to expand the exploration of Mandarin interjections and also to reveal the types and meanings of interjections by classifying them into categories according to the sentence context and tone. The data used in this research is the dialogue in the film My Old Classmate. Based on the meaning and purpose, interjections can generally be divided into several categories, namely emotive interjections, cognitive interjections and volitive interjections. This research uses a descriptive method, namely by accurately describing the types and meanings of interjections. Interjection forms found include 哦，哎，嗯，啊，我靠，哎呀，噢，嗨，哇，哇哦，喂，嘿，啊 天啊，哎呦，唉，唉呀，哎呦喂，and 哟. Based on the research results, it was found that the meaning of interjections that fall into the emotive category are expressions of anger, disappointment, surprise, joy; while those included in the cognitive category include expressing cognition or thoughts such as correcting an opinion, giving an assessment about someone, answering someone's call, questioning the truth of an assumption, and so on; Furthermore, those included in the volitive category include expressions that aim to persuade someone, such as asking someone to speak, asking someone to listen, asking someone to pay attention to something and so on. As for this study, teaching interjections in Mandarin language learning is very important and must be developed further.